The Biological and Chemical Diversity of Tetramic Acid Compounds from Marine-Derived Microorganisms - Jiang, Minghua (Mar Drugs, 2020)
Tetramic acid (pyrrolidine-2,4-dione) compounds, isolated from a variety of marine and terrestrial organisms, have attracted considerable attention for their diverse, challenging structural complexity and promising bioactivities. In the past decade, marine-derived microorganisms have become great repositories of novel tetramic acids. Here, we discuss the biological activities of 277 tetramic acids of eight classifications (simple 3-acyl tetramic acids, 3-oligoenoyltetramic acids, 3-decalinoyltetramic acid, 3-spirotetramic acids, macrocyclic tetramic acids, N-acylated tetramic acids, α-cyclopiazonic acid-type tetramic acids, and other tetramic acids) from marine-derived microbes, including fungi, actinobacteria, bacteria, and cyanobacteria, as reported in 195 research studies up to 2019.